3.7k views
4 votes
I really need help please, any Expert willing to help me out? I don’t understand on #2, for a,b, and c.

I really need help please, any Expert willing to help me out? I don’t understand on-example-1
User Slonkar
by
5.2k points

1 Answer

3 votes

Explanation:

a) Tangent equals sine divided by cosine. Therefore:

tan(-t) = sin(-t) / cos(-t)

b) Using the fact that sin(-t) = -sin(t) and cos(-t) = cos(t):

tan(-t) = -sin(t) / cos(t)

tan(-t) = -tan(t)

c) A function is symmetric about the origin if f(-x) = -f(x) (in other words, if it's an odd function). Therefore, y = tan(t) is symmetric about the origin.

User Cleber Goncalves
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.